Microstructure and mechanical properties of 3D-printed EH36 high strength low carbon steel - Peh, Zhi Hao (Nanyang Technological University, 2021)
Additive Manufacturing (AM) technologies have been growing and advancing over the years and different industries are adopting this technology to improve and maximize their manufacturing process. This process allows components with a complex geometric shape to be created with the use of computer aided design (CAD) software and the products manufactured from it could be used for various researches or applications. Marine and offshore (M&O) industry is one of the sector that has been utilising such technology to manufacture components. M&O industries often use High Strength Low Carbon steels such as API 5L X65 and ASTM A131 EH36 for their shipping construction and piping applications due to the great material properties of such materials. However, as additive manufacturing has provided many benefits, there are still limitations to products manufactured from this technology because of various factors such as defects or printing conditions affecting during the manufacturing process. Thus, in this project, the objective seeks to explore the microstructure and mechanical properties of 3D printed high strength low carbon steel printed using the direct laser deposition. This project mainly focuses on one material, ASTM A131 EH36, printed with wire used as the type of material deposition. The samples printed are printed in two orientations; XZ45° and XZ90°. Mechanical testing like the Tensile and Charpy Impact testing are conducted on the various printed samples in accordance to the ASTM standards and mechanical properties such as ultimate tensile strength (UTS), yield strength (YS) and ductility will be obtained for evaluation. Fractography and analysis of the microstructures will be investigated to relate the mechanical properties with any possible defects induced during the manufacturing process.